ATTITUDES OF FOOTBALL PLAYERS OF DIFFERENT AGE ON ILLEGAL STIMULANTS OF RECOVERY - Miroslav Smajić; Bogdan Tomić; Dragoljub Bekvalac (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Illegal stimulant use is considered a recovery or giving athletes a substance that artificially affects the improvement of physical and psychological condition of athletes and thus increase their success in sport. Consumption of materials that a healthy body can synthesize as hormones (testosterone, cortisone, growth hormone, etc.) falls under 164 CRNOGORSKA SPORTSKA AKADEMIJA, "Sport Mont" časopis br. 31,32,33. the concept of doping. Doping substances by their chemical composition and effect on the body of an athlete are different. The study aims to examine the attitudes of players of different ages on illegal stimulants of recovery. The sample comprised 120 players from nine different clubs from the area-level competition of the Football Association of Vojvodina (Serbian Super League = 43, first division = 40 Serbian and Serbian league = 37), which were divided into two groups according to age (group I (65 ) - 18-25 years age group II (55) - over 25 years of age). The sample of variables constitutes a system of 10 items (statements), and each paragraph (the claim) has five verbal categories. To determine the significance of differences between players of different ages multivariate analysis of variance were used (MANOVA), univariate analysis of variance (ANOVA), discriminative analysis, Roy's test, Pearson's coefficient of contingency (χ) and coefficient of multiple correlation (R). In general terms it can be concluded that the players of different ages do not differ and are unique to the approval of the proposed positions.